A relação entre inserção na informalidade e trabalho infantil no mercado de trabalho paranaense - Souza, Edicleia Lopes da Cruz (2011)
This paper aimed at analyzing the relationship between the insertion of an individual in informal labor and his/her work in childhood, starting from the assumption that the earlier an individual starts working, the greater is the probability of being inserted in informal activity in the labor market as an adult. Several researches have been developed on labor market to list and discuss its specificities and problems. There has been an increasing concern with the informality in this market and its impact on society, especially related to the difference between the wages and the work conditions among people who work regularly and the ones who do it informally. Beyond this, analyses about labor work are also concentrated on other forms of discrimination and illegality as well as on discussions about children and adolescents´ work and its consequences to the individual´s adulthood. According to National Household Sample Survey or PNAD/2009, 16.40% of children and adolescents from Parana State (BR), aged between 10 and 17, are workers and 24% of children from 5 to 9 years are inserted in the labor market, mainly performing household chores. Studies show that child labor is as harmful to the child in itself as it is to the society in general, especially on the individual´s education and qualification aspects. The research also point out that the low educational level is responsible for the workers insertion into the informal market, where they keep working without legal contract, under inadequate working conditions and earning lower salaries than the ones paid to the ones who work formally. Thus, it was for the present research to start a debate involving the relationship between both issues, since it was not found any similar study in the area. The analysis was carried out with the working people from Paraná state, aged from 18 to 70, based on data from PNAD/2009. It was used Descriptive Statistical analysis to verify and identify the main characteristics of the workers from Parana State, and the econometric model probit to capture the influence of those characteristics on their working conditions in the labor market, focusing on their age when they got started working. The statistical results, complemented by econometrical results reinforced the previous research hypothesis that the earlier an individual is inserted in the labor market, the greater is the probability of he or she is inserted in the informal work. It was found that 65.96% of the workers in Parana State were inserted in the labor market at 14. From these, 20.16% were younger than 9 years. Therefore, it is crucial that the country as a whole becomes aware of that children must be in school getting prepared for a better future and that the early work can cause irreversible damage to the society such as the perpetuation of the poverty and the informal work. Failing to realize the abuses suffered by the children and adolescents working so early, people are destroying the human capital necessary for the growth and the future development of economy.